Upaya Guru PAI Dalam Membentuk Sikap Hormat Siswa Di SMPS Dewantara - Rosdiana, Rosdiana; Lestari, Dini; Nur , Lutfiyah; Setiawan, Hasrian Rudi (Jurnal Pendidikan Islam Indonesia, 2025)
This study aims to examine the efforts of Islamic Religious Education (PAI) teachers in fostering students’ sense of respect toward teachers at SMPS Dewantara, Langkat. In the context of character education, respect is not merely understood as a form of politeness but as a fundamental moral value rooted in Islamic teachings. This research is motivated by the observed decline in students’ respectful attitudes, as reflected in daily behaviors such as a lack of courtesy and low levels of obedience toward teachers. This study employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The research subjects consist of PAI teachers and students. The collected data were analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that PAI teachers play a highly strategic role in instilling respectful attitudes in students, particularly through exemplary behavior, the habituation of positive conduct, the integration of religious values into the learning process, and emotional approaches that build close relationships with students. Students’ respect is demonstrated through behaviors such as greeting teachers, listening attentively, using polite language, and complying with school regulations. This study concludes that fostering respect requires the active involvement of teachers as well as support from a conducive school environment.